2009
DOI: 10.1159/000262328
|View full text |Cite
|
Sign up to set email alerts
|

Patient Physical Characteristics and Primary Care Physician Decision Making in Preconception Genetic Screening

Abstract: Background: There has been growing emphasis on preconception care as a strategy to improve maternal and child health since the 1980s. Increasingly, development of genetic tests will require primary care providers to make decisions about preconception genetic screening. Limited research has been conducted on how primary care providers interpret patients’ characteristics and use constructs, such as ethnicity and race, to decide whom to offer preconception genetic screening. Objective: This report assessed the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The panel is designed to target multiple ethnic populations by using broad disease panels and adding full gene sequencing, instead of being targeted to a specific ethnic group. In fact, some researchers have demonstrated that the use ethnic/racial labels provides little or no value when utilizing expanding carrier screening as opposed to panels targeted to specific ethnicities; thus, carrier screening of an expanded list of genetic conditions should be offered to all individuals regardless of their specific ethnic background …”
Section: Discussionmentioning
confidence: 99%
“…The panel is designed to target multiple ethnic populations by using broad disease panels and adding full gene sequencing, instead of being targeted to a specific ethnic group. In fact, some researchers have demonstrated that the use ethnic/racial labels provides little or no value when utilizing expanding carrier screening as opposed to panels targeted to specific ethnicities; thus, carrier screening of an expanded list of genetic conditions should be offered to all individuals regardless of their specific ethnic background …”
Section: Discussionmentioning
confidence: 99%
“…Although much of genetic counseling and testing has been guided by ethnic background, this paradigm has been challenged by the everincreasing ethnic admixture of patient populations, leading some researches to regard conventional racial/ethnic labels as being of little value. 20,21 This in turn has lent support to abolishing ethnicity/race-based recommendations for screening and using more comprehensive programs for universal screening. The movement toward universal screening, coupled with the reduced cost of simultaneously screening for multiple diseases, has led to changes in both expanded screening strategies and newborn screening.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Ashkenazi Jewish reporting, there are other factors to take into account as the concept of 'ethnicity' overlaps with religious, cultural, and historical considerations'' (9). Physicians also tend to rely on physical characteristics, such as skin color, to determine patient race/ethnicity, which can be highly inaccurate (12). These data suggest a need to replace ethnicity-based screening programs with more comprehensive programs that use expanded carrier screening to test for many disorders at the same time at a reduced cost compared with performing single gene tests.…”
mentioning
confidence: 99%